2020
DOI: 10.1080/01944363.2020.1791728
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Development Challenges in Western Gateway Communities

Abstract: Problem, research strategy, and findings: Small towns and cities outside of national parks, scenic public lands, and other natural amenities throughout the western United States are becoming increasingly popular places to live and visit. As a result, many of these gateway communities appear to be experiencing a range of pressures and challenges. In this study we draw on the results of in-depth interviews with 33 public officials and a survey of more than 300 public officials to shed light on the planning and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Certainly, in the development of this study, we identified a need for more examples of such work. While the idiosyncrasies of different socio-ecological systems make it difficult to directly export inferences about land use-change findings and apply them to another region, our primary drivers of development strategy and population growth are common concerns (Park & LaFrombois, 2019;Stoker et al, 2021) and the interactive dynamics our study found between our scenarios may be informative for application in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, in the development of this study, we identified a need for more examples of such work. While the idiosyncrasies of different socio-ecological systems make it difficult to directly export inferences about land use-change findings and apply them to another region, our primary drivers of development strategy and population growth are common concerns (Park & LaFrombois, 2019;Stoker et al, 2021) and the interactive dynamics our study found between our scenarios may be informative for application in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other corporations as well as some government and nonprofit organizations may do the same. Such decisions will have enormous implications for whether coronavirus pandemic refugees will return to expensive urban markets like New York City or whether they will seek out less dense suburban, exurban, and rural destinations with broadband access in the South and West regions of the country, creating, in the process, Zoom towns (Potter, 2020;Levine, 2020;Sen, 2020;Smith, 2020;Stoker, Rumore, Romaniello, & Levine, 2020).…”
Section: Discussion and Implications For Us Citiesmentioning
confidence: 99%
“…Media accounts and preliminary empirical research suggest that the response to the pandemic is no exception (Haynes, 2020;Patino, 2020;Allam, 2020;AFP Relaxnews, 2020;Stoker, Rumore, Romaniello, & Levine, 2020). Nearly a half million people reportedly fled hard-hit New York City within two months of the World Health Organization declaring the coronavirus disease a global pandemic (Horn, 2020;Hall, 2020;Frank, 2020;Sound Health and Lasting Wealth, n.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that gateway communities require deeper representation within conservation social science research [8,9]. Stoker et al (2021) distinguish IWGCs from other gateway communities as places of "150 to 25,000 people that are: (1) within 10 linear miles from the boundary of a national or state park or forest, major river or lake and (2) further than 15 miles from a census-designated urbanized area by road" ( [9], p. 23). This description was originated within the scope of the United States, referring to the western side of the Cascade and the Sierra Nevada Mountain ranges.…”
Section: Introductionmentioning
confidence: 99%